2002
DOI: 10.1093/jac/dkf008
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin suppresses lipopolysaccharide-induced interleukin-8 production by human monocytes through AP-1 and NF-kappaB transcription factors

Abstract: Erythromycin and other macrolides are effective for the treatment of chronic inflammatory airway diseases such as diffuse panbronchiolitis (DPB) and chronic sinusitis. The effect of macrolides in DPB is suggested to be anti-inflammatory rather than antibacterial. We investigated the effects of clarithromycin on interleukin-8 (IL-8) production using human peripheral monocytes and the human monocytic leukaemia cell line, THP-1. Bacterial extracts from Escherichia coli, Pseudomonas aeruginosa and Helicobacter pyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
127
0
13

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(152 citation statements)
references
References 31 publications
12
127
0
13
Order By: Relevance
“…However, only recently have investigators begun to elucidate the mechanisms by which such antibiotics counteract inflammation. These mechanisms may include the reduction of PMN and mononuclear leukocyte infiltration [25,31], the inhibition of pro-inflammatory cytokine expression in PMN, monocytes, and epithelial cells [24,27,32,44], the inhibition of PMN adhesion to epithelial cells [24,26], and the suppression of the PMN oxidative burst [15,32,45]. In addition, recent studies have demonstrated the ability of several macrolides and azalides, including erythromycin and azithromycin, to induce PMN apoptosis in vitro [7,16,20,28].…”
Section: Introductionmentioning
confidence: 99%
“…However, only recently have investigators begun to elucidate the mechanisms by which such antibiotics counteract inflammation. These mechanisms may include the reduction of PMN and mononuclear leukocyte infiltration [25,31], the inhibition of pro-inflammatory cytokine expression in PMN, monocytes, and epithelial cells [24,27,32,44], the inhibition of PMN adhesion to epithelial cells [24,26], and the suppression of the PMN oxidative burst [15,32,45]. In addition, recent studies have demonstrated the ability of several macrolides and azalides, including erythromycin and azithromycin, to induce PMN apoptosis in vitro [7,16,20,28].…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa penelitian menunjukkan bahwa tingkat eradikasi H. pylori lebih costeffective dibandingkan dengan terapi PPI ataupun H2-antagonis jangka panjang. 11,12 Pada saat penilaian dengan menggunakan endoskopi ditemukan juga kelainan pada tonsila lingualis berupa hipertrofi dan rinosinusitis. Juga didapatkan hipertrofi dan edema pada mukosa hidung dan sinus paranasal, disertai keluarnya sekret purulen yang persisten dan efusi sinus.…”
Section: -3unclassified
“…Macrolides, particularly those derived from 14-and 15-membered rings, exert antiinfammatory effects through a variety of signaling pathways including activator protein-1 (AP-1) and nuclear factor-kappaB (NF-ÎșB) (Sato et al 1998, Khan et al 1999, Desaki et al 2000, Rubin and Tamaoki 2000, Kikuchi et al 2002. The antibiotics have been reported to impair the production of pro-inflammatory cytokines (Kadota et al 1993, Fujii et al 1995.…”
Section: The Effect On Alpha-toxin-induced Deathmentioning
confidence: 99%